2019
DOI: 10.1016/j.jnoncrysol.2019.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Novel sol-gel SiO2-NaGdF4 transparent nano-glass-ceramics

Abstract: Novel transparent oxyfluoride nano-glass-ceramics containing undoped and 0.5 Eu 3+ (mol%) doped NaGdF 4 nanocrystals (NCs), were obtained by sol-gel for the first time. X-ray diffraction (XRD) confirms the precipitation of αand β-NaGdF 4 NCs with a size ranging between 5 and 24 nm. When the Na:Gd ratio, temperature and heating time are fixed to 0.95:1, 550-600°C and 1-8 h, respectively, only the β-NaGdF 4 phase precipitates. These results are confirmed by high-resolution transmission electron microscopy (HRTEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…On the other hand, the high melting temperatures of glass-forming components (e.g., 1450 • C, 1500 • C [37][38][39]) increase the risk of volatilization of the fluoride compounds, which may adversely affect the crystallization process of the fluoride fraction. Therefore, an alternative route to obtain oxyfluoride GCs is the sol-gel technique, characterized by low-temperature processing [40][41][42]. This method is based on hydrolysis, condensation and polycondensation reactions of organometallic precursors, usually alkoxysilanes Si(OR) 4 (R = -CH 3 , -C 2 H 5 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the high melting temperatures of glass-forming components (e.g., 1450 • C, 1500 • C [37][38][39]) increase the risk of volatilization of the fluoride compounds, which may adversely affect the crystallization process of the fluoride fraction. Therefore, an alternative route to obtain oxyfluoride GCs is the sol-gel technique, characterized by low-temperature processing [40][41][42]. This method is based on hydrolysis, condensation and polycondensation reactions of organometallic precursors, usually alkoxysilanes Si(OR) 4 (R = -CH 3 , -C 2 H 5 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The reports on the transparent oxyfluoride nano-glass-ceramics obtained by the annealing process of the silicate glasses can be also found in numerous publications of Durán et al [11,12,32,33,34]. The results obtained by Duran et al confirmed the incorporation of rare-earth in the nanocrystals (fluoride compounds) and explained their higher emission efficiency due to the lower phonon energy of the fluoride crystal lattice, which reduces the multi-phonon relaxation rates.…”
Section: Introductionmentioning
confidence: 99%
“…These GCs were fully transparent and homogeneous when heating the xerogels at 550 and 600 • C from 1 min to 8 h. Samples treated for >8 h appeared opaque due to larger NCs size or due to the formation of clusters. The structural analysis-XRD and HRTEM-confirmed the precipitation of NaGdF 4 NCs in two crystalline phases (cubic and/or hexagonal) with a size ranging between 4 and 24 nm, depending on the Na:Gd ratio, heating temperature, and time [78].…”
Section: Oxyfluoridegcsmentioning
confidence: 82%
“…For the last ten years, the GlaSS group at Ceramics and Glass Institute (CSIC) focused attention on the preparation of transparent glass-ceramics with low-phonon fluoride crystals, such as LaF 3 , NaGdF 4 , NaLuF 4 , KLaF 4 , etc., with rare-earth ions as dopants for optical applications [29,30,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. The main emphasis was on maximizing the crystalline fraction, maximum incorporation of the RE dopant, and further enhancement in luminescence profile.…”
Section: Oxyfluoridegcsmentioning
confidence: 99%